Initial Syriac Reading Book Syllabaire chaldéen - Anonymous, Anonymous (Analecta Gorgiana, 2010)
This small practice book for learning to read Syriac went through several printings at the Dominican Press in Mosul. It guides the reader through letter forms into words and then some practice reading passages